APPLICATION OF AIDCA COPYWRITING TECHNIQUES IN ADVERTISING CONTENT CREATION ON SOCIAL MEDIA : Case Study : PT Toekang Digital - astrid noviana paradhita; Myrtana Pusparisti (Jurnal Manajemen Bisnis dan Terapan, 2024)
Technological developments and people's consumption behavior have brought changes for industry players to introduce their products and services using digital marketing strategies. In its development, digital marketing has penetrated various media platforms, including social media. Copywriting is one method that can be used to create advertising content on social media. There are still many industry players who currently use digital agency services to make social media advertisements. However, quite a few were disappointed with the results obtained because even though they had paid a lot of money to create advertising content, no change or increase in sales was felt. This research aims to analyze the influence of applying AIDCA copywriting techniques on creating advertising content on social media. The study was carried out by applying qualitative descriptive methods. The results of this research show that applying the AIDCA technique to copywritten advertising content can increase traffic to the advertised product. Apart from that, implementing AIDCA can increase the actions of consumers who like, comment on, and share advertisements via consumer social media accounts.